Emerging technologies in neuromuscular ultrasound. Issue 6 (15th May 2020) - Hobson‐Webb, Lisa D.
Abstract: Neuromuscular ultrasound is an accepted and valuable element in the evaluation of peripheral nerve and muscle disease. However, ultrasound has several limitations to consider, including operator dependency and lack of a viable contrast agent. Fortunately, new technological advances show promise in resolving these issues. Ultra‐high resolution ultrasound enables imaging of the nerve at the fascicular level. Shear wave elastography imaging can provide measures of tissue stiffness that can act as a surrogate measure of nerve and muscle health. Photoacoustic imaging may overcome neuromuscular ultrasound's current lack of contrast agents to detect inflammation and other functional changes within nerve and muscle, while artificial intelligence stands to address operator dependency and improve diagnostic imaging. The basic principles of each of these technologies are discussed along with current research and potential future applications in neuromuscular imaging.